2006
DOI: 10.1007/s11103-005-5280-6
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional Gene Silencing of GBSSI in Potato: Effects of Size and Sequence of the Inverted Repeats

Abstract: In the past, silencing of granule-bound starch synthase (GBSSI) in potato was achieved by antisense technology, where it was observed that inclusion of the 3' end of the GBSSI coding region increased silencing efficiency. Since higher silencing efficiencies were desired, GBSSI inverted repeat constructs were designed and tested in potato. First, large inverted repeats comprising the 5' and the 3' half of the GBSSI cDNA were tested. The 5' IR construct gave a significantly higher silencing efficiency than the 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 55 publications
3
26
0
1
Order By: Relevance
“…Figure 3B shows that no signal was present in transformants of IR MA-S, while transformants of IR MS-A did show hybridisation of siRNAs with probe A. From previous work, it was known that all these transformants, except the non-silenced transformant IR MA-S-26, showed accumulation of GBSSI siRNAs after hybridisation with the MF1+MR1 PCR product of the GBSSI cDNA as a probe (Heilersig et al 2006). Therefore, the lack of hybridisation with the spacer probe in transformants of IR MA-S indicates that no siRNAs of spacer sequences are formed.…”
Section: Effect Of An Intron In the Spacer Sequence On Silencing Effimentioning
confidence: 84%
See 1 more Smart Citation
“…Figure 3B shows that no signal was present in transformants of IR MA-S, while transformants of IR MS-A did show hybridisation of siRNAs with probe A. From previous work, it was known that all these transformants, except the non-silenced transformant IR MA-S-26, showed accumulation of GBSSI siRNAs after hybridisation with the MF1+MR1 PCR product of the GBSSI cDNA as a probe (Heilersig et al 2006). Therefore, the lack of hybridisation with the spacer probe in transformants of IR MA-S indicates that no siRNAs of spacer sequences are formed.…”
Section: Effect Of An Intron In the Spacer Sequence On Silencing Effimentioning
confidence: 84%
“…GBSSI cDNA inverted repeat constructs were made as described by Heilersig et al (2006). The GBSSI cDNA (Visser et al 1989; sequence deduced from the genomic sequence published by van der Leij et al 1991) was divided in three regions; the 5¢, the middle and the 3¢ region.…”
Section: Dna Constructsmentioning
confidence: 99%
“…However, although transformants obtained using antisense or invertedrepeat constructs show strong silencing of GBSSI, GBSSI mRNA remained present (Kuipers et al 1994, Heilersig et al 2006a. To obtain a transformant with no GBSSI mRNA, TGS technology has been used, while to induce allele-specific silencing, TGS could also be a good approach, since the four classes of GBSSI alleles are highly homologous in the coding region but vary in their promoter sequences (van de Wal et al 2001).…”
Section: Transgene-induced Epigenetic Variationmentioning
confidence: 99%
“…al. 14 showed that size and sequence of inverted repeats sequences had an effect on silencing efficiency. Ichihara et.…”
Section: Introductionmentioning
confidence: 99%